2023
DOI: 10.1098/rsbl.2023.0126
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence of an increased susceptibility to face pareidolia in postpartum women

Jessica Taubert,
Samantha Wally,
Barnaby J. Dixson

Abstract: As primates, we are hypersensitive to faces and face-like patterns in the visual environment, hence we often perceive illusory faces in otherwise inanimate objects, such as burnt pieces of toast and the surface of the moon. Although this phenomenon, known as face pareidolia, is a common experience, it is unknown whether our susceptibility to face pareidolia is static across our lifespan or what factors would cause it to change. Given the evidence that behaviour towards face stimuli is modulated by the neuropep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…1 B). This nested design has been exploited in previous studies of ambient face pareidolia because it means any differences in the behavioral or neural correlates are driven by the presence of illusory facial features 7 , 9 11 , 14 , 19 , 21 , 23 , 24 , 36 . Thus, the current results suggest that the advantage for faces in the fast saccadic choice paradigm is supported, at least in part, but the visual information that real and illusory faces share in common.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 B). This nested design has been exploited in previous studies of ambient face pareidolia because it means any differences in the behavioral or neural correlates are driven by the presence of illusory facial features 7 , 9 11 , 14 , 19 , 21 , 23 , 24 , 36 . Thus, the current results suggest that the advantage for faces in the fast saccadic choice paradigm is supported, at least in part, but the visual information that real and illusory faces share in common.…”
Section: Resultsmentioning
confidence: 99%
“…A number of researchers have previously described variation in the strength of the illusory percept in examples of face pareidolia 19 , 21 , 37 and although there have been numerous attempts to determine the source of this variation using models of low-level saliency, curvature and dominant spatial structure 9 , 19 , 37 as well as deep neural networks trained on large image sets 9 , 19 , none of these models have been able to predict face pareidolia illusion, perhaps owning to their high-degree of visual variability among examples of face pareidolia. For example, face pareidolia can occur on the side of a building, in a multi-colored burger being held in two hands or a small, green button.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 2B ( left ), we have plotted the average “face scores” for the experimental stimuli as a function of their gender and expression conditions. These scores were derived from independent data ( N = 800) shared by Wardle et al (2022) and are thought to describe the strength of the face pareidolia illusion (Taubert et al, 2023; Wardle et al, 2022). When we compared the happy, female stimuli ( M = 7.18, SE = 0.42) to the angry, female stimuli ( M = 6.17, SE = 0.79) using an independent-samples t test (two-tailed), we found no evidence of a difference in illusory strength between the two groups, t (14) = 1.13, p = .28; Figure 2B, left .…”
Section: Resultsmentioning
confidence: 99%
“…Illusory Strength (Stimulus Ambiguity) Wardle et al (2022) and others (Taubert et al, 2023;Wardle et al, 2020) have demonstrated that ambient examples of face pareidolia vary greatly in their illusory strength. Could the results in Figure 1 reflect the fidelity of the illusory face or the illusory expression?…”
Section: Ratings Datamentioning
confidence: 99%